Synthesis of closo-CB11H12– Salts Using Common Laboratory ReagentsClick to copy article link - Berger, Amanda; Buckley, Craig; Paskevicius, Mark (AMER CHEMICAL SOC, 2021)
Lithium and sodium salts of the closo-carbadodecaborate anion [CB11H12]- have been shown to form stable solid-state electrolytes with excellent ionic conductivity for all-solid-state batteries (ASSB). However, potential commercial application is currently hindered by the difficult, low-yielding, and expensive synthetic pathways. We report a novel and cost-effective method to synthesize the [CB11H12]- anion in a 40% yield from [B11H14]-, which can be synthesized using common laboratory reagents. The method avoids the use of expensive and dangerous reagents such as NaH, decaborane, and CF3SiMe3 and shows excellent reproducibility in product yield and purity.